IMPLEMENTASI METODE PEMBELAJARAN AFEKTIF DALAM PEMBENTUKAN SIKAP MULTIKULTURAL SISWA DI MIN 3 WAY KANAN - Septiani, Gunik; Umi, Muflikhah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This research is qualitative research because it is aimed at finding out in-depth information regarding the implementation of multicultural education at MIN 3 Way Kanan, especially regarding learning methods in multicultural education to form students' multicultural attitudes. Affective learning methods in multicultural education at MIN 3 Way Kanan can be classified into two types. First, the learning methods that take place during the learning process in the classroom. Second, learning methods that take place outside of classroom learning. The learning methods that take place during classroom learning are usually related to the subject matter being taught, such as learning design by playing roles in drama, group learning systems, and also learning systems through presentations. Apart from learning methods that are directly related to the subject matter, there are also programs at MIN 3 Way Kanan that can be used as a means of instilling multicultural values ??in students. These programs include opening classes, a class mixing system, and a rolling system or rotation of student seats. Meanwhile, multicultural learning methods that take place outside of classroom learning are usually through certain events held at MIN 3 Way Kanan. These events include Kartini Day, commemoration of Islamic holidays, which showcase the culture of each region. The implementation of affective learning methods plays a role in the internalization of multicultural values. Through the affective learning method used, students' multicultural attitudes can be formed, such as attitudes of tolerance and respect, anti-bullying attitudes, and the ability to adapt to new environments. This of course cannot be separated from the role of teachers who play a role in providing direction, guidance, role models and building awareness of the importance of tolerance and respect for students. With the existence of affective learning methods which tend to predominantly involve students actively, it can make it easier to instill multicultural values ??in students.